PENINGKATAN PARTISIPASI AKREDITASI MELALUI PELATIHAN DAN PENDAMPINGAN PENYUSUNAN DOKUMEN AKREDITASI DELAPAN STANDAR - Fuad Hasan; Linda Fajarwati; David Imamyartha (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The reasons Pusat Kegiatan Belajar Masyarakat (PKBM)/Community Learning Center especially in regency of Jember has low participation in proposing the accreditation is luck of understanding about accreditation and the luck of document that is needed to proceed accreditation. This community services activity is to provide the information about non formal education accreditation and to guide in compiling accreditation document. This activity is formatting into training and mentoring activity. The result of this activity is the readiness of PKBM in proposing the piloting program which is showed by the completion in compiling the document national education standard and the completion in full filling the document into the accreditation information and evaluation system called SISPENA. Moreover two of the PKBM that is become the object of this activity has success in become the target of accreditation instrument testing and piloting. Generally, it can be conclude that this community services activity has big success, so the number of PKBM that become the object of community services should be increased